VIII ALL-RUSSIAN CONFERENCE ON ATMOSPHERIC ELECTRICITY - P.P. Firstov; V. I Kozlov; E. I. Malkin (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2019)
From September 23 to September 27, 2019, the VIII All-Russian Conference on Atmospheric Electricity was held in Nalchik. The conference was organized by the Russian Academy of Sciences, the A.F. Mozhaisk (All-Russian Academy of Sciences named after AF Mozhaisk) and the High Mountain Geophysical Institute of Roshydromet (VGI). This article describes the work of the conference and some of the provisions of the conference decision.